INVESTIGATION OF COCOA HUSKS DENSIFICATION POSSIBILITIES - Križan, Peter; Matúš, Miloš; Bábics, Jozef; Beniak, Juraj (International Journal of Research -GRANTHAALAYAH, 2022)
During the biomass densification can be recognized various technological variables and also material parameters which significantly influences the final solid biofuels (pellets, briquettes) quality. In this paper, we will present the research findings concerning relationships between technological and material variables during densification of cocoa husks. Cocoa husks, as an unused raw feedstock after chocolate production, is a typical product of food factory. The main goal of presented experimental research is to determine the effect of compression pressure and material particle size on final biofuels quality, and thus investigate the possibilities for densification of cocoa husks. Experimental research described in this paper was realized by single-axis densification, which was represented by experimental pressing stand. The effect of mentioned investigated variables on the final pellets density was determined. Mutual interactions of these variables on final pellets quality are showing the importance of mentioned variables during the densification process. Impact of raw material particle size on final biofuels quality was also proven by experimental research on semi-production pelleting plant. Research findings dealing with pelleting and briquetting possibilities are included.